2018
DOI: 10.5539/ibr.v11n8p142
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Innovation on Entrepreneurial Competencies and Business Success in Malaysian SMEs

Abstract: The purpose of this paper is to explore the extent of entrepreneurial competencies and innovation on business success in SMEs in Malaysia. Specifically, this study tested the mediating role of product innovation and process innovation between the relationship of entrepreneurial competencies and business success. The statical sample population of this research includes 407 owner and manager involved in SMEs, both manufacturing and services & other sectors. For data collection, a standard questionnaire u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(39 reference statements)
3
9
1
1
Order By: Relevance
“…The results of this study certainly do not support a previous research conducted by Umar et al (2018) which stated that process innovation and product innovation can partially mediate the influence of entrepreneurial competence on financial and non-financial business performance. This difference in results was probably due to previous research was carried out in normal conditions, while this study was conducted during the COVID-19 pandemic.…”
Section: The Influence Of Competence On Fashion Business Performance In Surabaya With Work Innovation As a Mediating Variable During The contrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study certainly do not support a previous research conducted by Umar et al (2018) which stated that process innovation and product innovation can partially mediate the influence of entrepreneurial competence on financial and non-financial business performance. This difference in results was probably due to previous research was carried out in normal conditions, while this study was conducted during the COVID-19 pandemic.…”
Section: The Influence Of Competence On Fashion Business Performance In Surabaya With Work Innovation As a Mediating Variable During The contrasting
confidence: 99%
“…Work innovation is defined as an effort made by utilizing all available resources to develop ideas, solve problems in order to survive, and create new products. Previous study was conducted by Umar, et al (2018) on 407 business owners as well as business managers in fields of manufacturing, services, and others in Malaysia. The study found that process innovation and product innovation can partially mediate the effect of entrepreneurial competence on financial and nonfinancial business performance.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the greater level of the identified competencies, the higher level of social innovation development of the enterprises. Umar et al (2018) also reveals the study findings that exhibited a positive relationship between entrepreneurial competencies, innovation development and business success of small and medium enterprises (SMEs) in Malaysia. This is also consistent with a study of Varis and Littunen (2010) that demonstrated the positive association between personal competencies in terms of information-seeking and a firm's innovation development and growth sustainability.…”
Section: Discussionsupporting
confidence: 54%
“…Sa'ari, Adenan, Hashim, and Jamaludin (2013) confirmed that entrepreneurial competencies have led to high performance in the organisation and gained competitive advantages over the competitors. This is seconded by recent study done by Umar et al (2018) urged that entrepreneurial competencies significantly affect the performance in Malaysian SMEs as well the innovation practice in the firm. Another research conducted by Mitchelmore and Rowley (2010), claimed that entrepreneurial competencies can range from personality traits and individual motivations to specific knowledge and the skills.…”
Section: Introductionmentioning
confidence: 95%